2014
DOI: 10.1371/journal.pone.0115176
|View full text |Cite
|
Sign up to set email alerts
|

Autophagic Marker MAP1LC3B Expression Levels Are Associated with Carotid Atherosclerosis Symptomatology

Abstract: ObjectivesThe mechanism by which atheroma plaque becomes unstable is not completely understood to date but analysis of differentially expressed genes in stable versus unstable plaques may provide clues. This will be crucial toward disclosing the mechanistic basis of plaque instability, and may help to identify prognostic biomarkers for ischaemic events. The objective of our study was to identify differences in expression levels of 59 selected genes between symptomatic patients (unstable plaques) and asymptomat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 50 publications
1
30
0
Order By: Relevance
“…50 Importantly, these SNPs are also in proximity to IL12B, a gene previously associated with both TB 9,51 and leprosy. 52 IL12B variants have also been associated with carotid stenosis 53 and psoriasis, 54 possibly owing to LD with SNPs in UBLCP1. IL12B encodes p40, one of two subunits of interleukin-12 (IL-12) 55 and IL-23.…”
Section: Discussionmentioning
confidence: 99%
“…50 Importantly, these SNPs are also in proximity to IL12B, a gene previously associated with both TB 9,51 and leprosy. 52 IL12B variants have also been associated with carotid stenosis 53 and psoriasis, 54 possibly owing to LD with SNPs in UBLCP1. IL12B encodes p40, one of two subunits of interleukin-12 (IL-12) 55 and IL-23.…”
Section: Discussionmentioning
confidence: 99%
“…In the last 10 years, various methods have been applied to assess autophagy in cells that form atherosclerotic plaques (VSMCs, endothelial cells, macrophages), including electron microscopy, fluorescence microscopy and western blot approaches [44,45]. Studies conducted on human specimens and mouse models of AS have reported either dysfunctional or decreased autophagy based on detection of the autophagic markers p62 and LC3-II in cells isolated from plaques [46][47][48]. Indeed, a strong decrease in LC3-II expression has been reported in patients with unstable plaques compared to those with stable plaques [48]; such decreases would enable dead cell accumulation in the artery wall and subsequent plaque destabilization ( Figure 2).…”
Section: Atherosclerosismentioning
confidence: 99%
“…Studies conducted on human specimens and mouse models of AS have reported either dysfunctional or decreased autophagy based on detection of the autophagic markers p62 and LC3-II in cells isolated from plaques [46][47][48]. Indeed, a strong decrease in LC3-II expression has been reported in patients with unstable plaques compared to those with stable plaques [48]; such decreases would enable dead cell accumulation in the artery wall and subsequent plaque destabilization ( Figure 2). A dysfunction in the autophagic process, caused by either autophagy related 7 (ATG7) deletion in VSMCs [49,50] or a macrophage-specific ATG5-null mutant mouse model [46], has been linked to atheroma development in AS.…”
Section: Atherosclerosismentioning
confidence: 99%
“…DAPK1 and ATG10, which stimulate autophagy [16,17], were activated, whereas several genes known to activate autophagy, such as DRAM1, ULK2, BCL2L1, EPG5, and NPC1, were suppressed in ELK3 KD [18][19][20][21][22][23][24][25] (Fig. 1A).…”
Section: Autophagy Is Impaired By Suppression Of Elk3 In Mda-mb-231 Cmentioning
confidence: 99%